KERUSAKAN TEGAKAN TINGGAL AKIBAT KEGIATAN PEMANENAN DI AREAL IUPHHK-HA PT. KALIMANTAN SATYA KENCANA KALIMANTAN BARAT - jar, Sani; Manurung, Togar Fernando; Yani, Ahmad (JURNAL HUTAN LESTARI, 2013)
This research was conducted in IUPHHK-HA PT. Kalimantan Satya Kencana, it aims to have the percentation of the damaged residual stands after the harvesting, and it also aims to determine the relationship between the (LBDS) of harvesting trees. This research is done an 9 plots with the 100 x 100 m2 size, and its place with the methods called line plot sampling with random start. The damage of the resudual stand of seedling is 26.39%, sapling 27.98% ,pole 26.34%, and tree 20.77%. The damage level of the residual stand is catagorized in heavy (70.63%, 37.07%), medium (17.81%, 38.23), and low (11.56%; 24.70 ). The relationship between the harvested trees LBDS and the damaged residual trees shows a highly significant and positively correlated. More larger of the trees LBDS then the damage will be higher. Keywords: LBDS, harvesting, residual stands damaged, seedling, sapling, pole, tree.